2013
DOI: 10.1080/09602011.2012.724355
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory in multiple sclerosis patients: Assessment and cognitive facilitation

Abstract: The multifocal nature of lesions in multiple sclerosis hints at the occurrence of autobiographical memory (AbM) impairment. However, the dearth of studies on AbM in multiple sclerosis is noticeable, notwithstanding the importance of AbM in everyday life. In the first section of this study, 25 multiple sclerosis patients and 35 controls underwent a detailed episodic AbM assessment. Results obtained by means of ANOVA suggested an AbM retrieval deficit in every patient. That pattern of performance paved the way f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 72 publications
5
33
2
Order By: Relevance
“…In keeping with previous studies (Ernst et al, 2013 patients from the experimental group showed improved AM performance after facilitation, with an effective transfer of benefits to daily functioning (see also . The benefit of the MVI programme was specific to internal details, namely details that are episodic in nature, which were the primary focus of this intervention.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…In keeping with previous studies (Ernst et al, 2013 patients from the experimental group showed improved AM performance after facilitation, with an effective transfer of benefits to daily functioning (see also . The benefit of the MVI programme was specific to internal details, namely details that are episodic in nature, which were the primary focus of this intervention.…”
Section: Discussionsupporting
confidence: 50%
“…Ernst et al (2013 obtained the first results using this programme and reported positive outcomes on AM functioning that was accompanied by an effective transfer in daily life functioning, counteracting the deleterious impact of AM impairment previously reported by the patients, and with a long-term robustness of treatment effect.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations